PENERAPAN LOGIKA FUZZY DALAM SISTEM PENDUKUNG KEPUTUSAN PEMBERIAN BEASISWA BSM - Yunita Yunita (Jurnal Techno Nusa Mandiri, 2016)
The selection process elections BSM students receiving Academic includes three variables, namely, income and number of siblings Parents bladder. After processing of the above variables will result in decisions that students deserve a BSM, Worthy or Not Worthy. In order to produce a fast and accurate decision and to avoid any mistakes in the selection of students, it needs an appropriate method that can be used to assist decision makers in carrying out their duties. By using the right method then the School Committee will be easier to make decisions. The method is considered to overcome this problem is through a fuzzy logic approach to the method of Sugeno Order 0. The end result of this study is the result that states a student eligible to get a scholarship for BSM, for which data are available.